ITZ microanalysis of cement-based building materials with incorporation of siderurgical aggregates. (15th May 2023) - Aghajanian, A.; Cimentada, A.; Fayyaz, M.; Brand, A.S.; Thomas, C.
Abstract: With the depletion of natural resources, it is essential to use recycled materials and industrial wastes to adapt the expanding building sector to the environment. Slag from electric arc furnaces is one example that can be used as a siderurgical aggregate in concrete production. Studying the interfacial transition zone between the aggregate and the binder is necessary because the reaction between the aggregate and the binder can significantly impact the concrete's microstructure and mechanical properties. In order to examine any concrete sample with any physical or chemical structure, this study introduces the instruments used to conduct these studies and the methods for preparing concrete samples for the desired area. The results show that solvent exchange with Ethanol is the best method for draining water from the inner surface of the sample in the interfacial transition zone (ITZ) with minimal destruction. Also, the kind of sample and its information determine the type of coating that should be applied. Gold is the best choice to examine the topography of the sample surface because it has a higher electron return coefficient than other elements and produces images of higher quality. The epoxy with a viscosity of 550 cP (20 °C) or 150 cP (50 °C), a maximum curing temperature of 50 °C, a curing time of 8 h, and an epoxy-to-hardener ratio of 25 to 3 g is the best configuration for having the best sample for microanalysis. Highlights: The SEM, TEM, and SPM electron microscope imaging techniques were described. Investigating was the best way to prepare samples for microscopic photography. It was explained how to polish the sample for the best microscopic image. The amount and process for using gold as a conductor for electronic photography were described. The impact of scratches on the sample surface was examined in microscopic electronic photos.